From acyclic to cyclic α-amino vinylphosphonates by using ring-closing metathesis. Issue 2 (5th December 2016) - Adler, Pauline; Fadel, Antoine; Prunet, Joëlle; Rabasso, Nicolas
Abstract : Acyclic α-amino vinylphosphonates were alkylated through the Mitsunobu reaction then diolefinic compounds hence formed were subjected to RCM. Abstract : Acyclic α-amino vinylphosphonates were alkylated through the Mitsunobu reaction then diolefinic compounds hence formed were subjected to RCM. Studies on the scope and limitations of RCM with these sterically hindered α-amino vinylphosphonates are detailed.